University students' graph interpretation and comprehension abilities. (2nd October 2019) - Bragdon, Daniel; Pandiscio, Eric; Speer, Natasha
ABSTRACT: An executive report to the President of the United States titled Engaging to Excel: Producing One Million Additional College Graduates with Degrees in Science, predicted that over the next decade, the United States will lack college graduates in the fields of science, technology, engineering, and mathematics (STEM). One contributing factor is university students' weak command of the mathematics needed to study STEM. Algebra is a foundational content area of mathematics and necessary for developing the concept of a function, with linear functions being the most basic form. To understand student learning and to inform improvements to instruction, we investigated university students' abilities and skills associated with linear graph comprehension. Findings indicate that university students do have difficulties with linear graph comprehension, specifically when predicting a value not given by the graph. Interviews were used to examine participants' solution methods, and their choice of solution method was found not to be a predictor of success. Implications for instruction and further research are discussed.